Combined Lifestyle Factors and Risk of All-Cause and Cause-Specific Mortality Among Participants in the Linxian Nutrition Intervention Trial: A Cohort, Observational Study - Fan, Jin-hu; Wang, Jian-bing; Yang, Huan; Dawsey, Sanford M.; Taylor, Philip R.; Qiao, You-lin; Abnet, Christian C. (Frontiers in Cardiovascular Medicine, 2022)
Background Several studies have indicated that combinations of lifestyle and dietary factors are associated with risk of total mortality and death from cardiovascular disease and cancer, but limited data are available from long-term follow-up studies in China. Methods This study was a observational cohort study. We prospectively examined the associations of combined lifestyle factors and risk of total and cause-specific mortality in the Linxian General Population Nutrition Intervention Trial (NIT) cohort that included 29,584 healthy adults. A points system method was used to calculate a combined risk score of five lifestyle factors, including smoking, alcohol drinking, body mass index, vegetable intake and fruit intake. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs). Results Overall, adjusted hazard ratios for mortality increased progressively with an increasing combined risk score. Compared to individuals with a score of zero or one, HRs (95%CIs) for a score of five or above were 1.59 (1.44–1.75) for all-cause mortality, 1.67 (1.48–1.88) for heart disease, 1.69 (1.52–1.88) for stroke, and 1.34 (1.21, 1.47) for cancer. This association for mortality was seen consistently, regardless of gender and age at baseline. Conclusions A higher combined risk score was positively associated with risk of total, heart disease, stroke, and cancer mortality. These findings could provide further evidence for the idea that healthy lifestyle is the optimal way to reduce the risk of premature death, and encourage behavior change.